Literasi Akuntansi Rumah Tangga Untuk Menekan Risiko Kemiskinan Pada Kelompok PKK Nambo - Nur Asni; Hasbudin Hasbudin; Husin Husin; Intihanah Intihanah; Tuti Darmawati; Emillia Nurdin; Rahmi Syafitri; Adhanti Eka Fitriyani; Nurul Chomariah Agustin (Jurnal Pemberdayaan Nusantara, 2026)
This community service program aimed to strengthen household accounting literacy among housewives in the PKK group of Kelurahan Nambo, Kecamatan Nambo, Southeast Sulawesi, as a strategy to reduce household poverty risk. The method combined participatory adult-learning lectures, case simulations, small-group discussion, and four weeks of hands-on mentoring in filling household cash books, debt-monitoring cards, and monthly evaluation sheets. The program was attended by housewives active in PKK activities, with pre-test and post-test used to measure knowledge gains. Results showed an increase in participants' understanding of budgeting, cash-flow recording, and emergency-fund planning, along with growing ability to separate household and side-business funds. The program is recommended to continue through periodic mentoring by local PKK cadres to sustain behavioral change.